Ethnic minorities’ and immigrants’ therapeutic (non)adherence: what is the role of social and cultural contexts? - Mourão, S. (2015)
Immigrants and ethnic minorities have been identified as vulnerable groups in health, in general, and in what concerns therapeutic non-adherence (TA) in particular; i.e., (not)following health-care providers’ therapeutic recommendations. The general aim of this paper is presenting a literature review of immigrants’/ethnic minorities’ TA determinants. We will start by highlighting the reasons as to why immigrants’/ethnic minorities’ therapeutic (non)adherence should be a topic of concern. Then, we will present a review of the main determinants of immigrants’/ethnic minorities’TA, at different levels of analysis (e.g., broad structural level; social and community networks; material and social conditions) and emphasize that non-adherence among immigrants/ethnic minorities is mostly non-intentional, seeing as how it is associated with issues such as: low socio-economic conditions, language barriers and cultural mismatches. Finally, we will highlight the role of health-care providers in tackling this health-related problem and reflect about the importance of promoting development and training of health-care providers’ multicultural abilities. Os imigrantes e as minorias étnicas têm sido identificados como grupos vulneráveis na área da saúde, em geral, e no que diz respeito à (não)adesão terapêutica, em particular, i.e., (não)seguimento das recomendações dos profissionais de saúde. O objetivo geral deste artigo é o de apresentar uma revisão de literatura sobre os determinantes da (não)adesão terapêutica de imigrantes e minorias étnicas. Inicialmente, destacar-se-ão os motivos pelos quais a (não)adesão terapêutica de imigrantes/minorias étnicas poderá ser considerada como um tema relevante. Seguidamente, apresentar-se-á uma revisão sobre os principais determinantes da (não)adesão de imigrantes/minorias étnicas, em diferentes níveis de análise (e.g., estrutural; redes sociais e comunitárias; condições materiais e sociais) e destacar-se-á que a não-adesão entre os imigrantes/minorias étnicas é sobretudo não-intencional, por se encontrar associada a questões como: condições socioeconómicas desfavoráveis, barreiras linguísticas, desen contros culturais. Finalmente, salientar-se-á o papel dos profissionais de saúde na resolução deste problema relacionado com a saúde e reflectir-se-á sobre a importância de promover o desenvolvimento e a formação de competências multiculturais por estes profissionais.